ISSUES AND CHALLENGES IN THE IMPLEMENTATION OF THE INTEGRATION OF KNOWLEDGE IN ISLAM IN NIGERIAN UNIVERSITIES - Aliyu Idris; Prof. Dr. Mohd Nor Bin Nawawi (Journal of Islamic, Social, Economics and Development, 2021)
The study was aimed to highlight the concept of integration of Knowledge in Islam and the challenges confronting the smooth implementation of the concept in Bayero University, Kano, Nigeria. The integration of knowledge is a concept which can be applied by the educational sector in order to create a sound generation of multidisciplinary knowledge. The concept of integration of knowledge can be define as a union of two or more sectors as a merger or combination of both western and Islamic knowledge. Muslims were mandated to seek for knowledge, which includes various forms of knowledge such as Aqidah, Shariah, Moral, Ethics and others. Mastering the Islamic knowledge along with the western knowledge may lead to the emergence of contemporary knowledge based on the Islamic principles. Islam has encouraged the Muslims to seek for knowledge in all the fields that will assist the humanity. The Study adopted the qualitative research is conducted in order to have better understanding on the interpretations and meaning that people give to events, objects and other people in their environmental contexts. The Paper conclude that the application of western knowledge leads to the spread of secular influence in the educational system of a nation, which in turn leads to the gradual loss of Islamic identity of the society. Therefore, the approach to the integration of Islamic knowledge and that of the West needs to be seen as an alternative for the society in leading their everyday lives based on the true teachings of Islam.